Determination of Streptomyces sp. SAE4034 Antioxidant and Antibacterial Compound and Its Inhibitory Mechanism on Staphylococcus aureus - Kurniawati, Pratiwi Kusuma; Ryandini, Dini; Hernayanti, Hernayanti (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The genus Streptomyces is known as producers of bioactive compounds that have antibacterial and antioxidant properties. Streptomyces sp. SAE4034 was known to produce antibacterial compounds that can inhibit and kill pathogenic bacteria, including Staphylococcus aureus, but the group of antibacterial compounds and their inhibitory mechanisms were not yet known. The ability of Streptomyces sp. SAE4034 in producing antioxidants is unknown yet. This research aimed to determine the classification of antibacterial compounds produced by Streptomyces sp. SAE4034, its potency in producing antioxidant compounds, and to observe the inhibitory mechanisms of antibacterial compounds produced by Streptomyces sp. SAE4034 against S. aureus using cell leakage method. The results of this research showed that Streptomyces sp. SAE4034 produce compounds in the groups of alkaloid, terpenoid, flavonoid, and polyphenol. Compounds with Rf values 0.40 and 0.47 which includes into polyphenol and 0.72 which includes into alkaloid group has the ability to inhibit the growth of S. aureus. The MIC value was 256 μg/mL. Streptomyces sp. SAE4034 has a very strong antioxidant activity that can scavenge DPPH free radical with IC50value of 32,14 ppm and has an antioxidant enzyme activity that is superoxide dismutase amount of 63,10 U/mL The inhibition mechanism of Streptomyces sp. SAE4034 crude extract against S. aureus was through leaking of the cell wall or cell membrane resulting in the release of nucleic acid and protein of S. aureus cells and the highest cell leakage was at 2 doses of MIC.